George C. Powell correspondence - Powell, George C.
ALsS (1865 November 7 and 1866 March 4) from Powell, of Live Oak, East Fla., to Baptist minister A.D. Gillette regarding Powell's son, Lewis Payne (Lewis Thornton Powell), following Payne's execution as a co-conspirator in the attempt to assassinate Abraham Lincoln. Powell expresses gratitude to Gillette for his kindness to Lewis and requests that Gillette send his son's remains as well as any articles left by his son to Powell's home in Florida. Powell also mentions his son's Civil War service as a soldier in the Confederate Army.
Clergyman. Father of Lewis Payne (Lewis Thornton Powell).
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Gillette, A. D. -- 1807-1882 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Assassination; Payne, Lewis, -- 1845-1865.; Confederate States of America. -- Army; United States -- History -- Civil War, 1861-1865.; Clergy